Visualeadership leveraging the power of visual thinking in leadership and in life - Cherches, Todd (Gildan Audio, 2020)
VisuaLeadership [noun]: The art and science of applying visual thinking and visual communication tools, tips, and techniques, in order to turn your vision into reality.If a picture is worth a thousand words, and finding the right words takes time, and time is money, then wouldn't it follow that business leaders could make more money-in less time-if they simply took a more "visual" approach to how they manage and lead'Okay, it's not quite that simple ... but VisuaLeadership will forever change the way you think and communicate by showing how you can quickly and easily leverage the power of visual imagery, mental models, metaphor, analogy, storytelling, and humor to help you take your game to a whole new level.The French novelist Marcel Proust famously wrote that, "The real voyage of discovery consists not in seeking new lands, but in seeing with new eyes." So, if your vision is to become a better communicator and presenter, a more innovative thinker, a more productive performer, a more efficient manager, a more effective coach, or a more visionary and inspirational leader, then this exciting new book will open your "mind's eye" to a whole new world: the world of VisuaLeadership.